Freestyle wrestlers reaction time differences between different wrestling specific visual stimuli and kinetic responses - Gkrekidis, A.; Nikolopoulos, G.; Gkagka, P.; Barbas, I.; Menychtas, D.; Giannakou, E.; Aggeloussis, N. (International Journal of Wrestling Science, 2023)
PURPOSE of the current study was to examine the differences between the reaction time of wrestlers attacking the left leg, the right leg or both legs given a different kinetic visual stimulus.